Study of the possibilities of non-invasive assessment of increased intracranial pressure according to MRI data on the example of patients with secondary intracranial hypertension - N. N. Sidikov; O. B. Bogomyakova; Yu. A. Stankevich; A. A. Tulupov (Сибирский научный медицинский журнал, 2024)
Modern methods of neuroimaging make it possible to develop approaches for assessing intracranial pressure as a replacement for the “gold standard” of invasive monitoring. Aim of the study was to investigate the possibility of using magnetic resonance (MR) characteristics to assess the increase in intracranial pressure in patients with secondary intracranial hypertension. Material and methods. Group 1 – 40 patients with brain tumors, group 2 – 15 patients with communicating hydrocephalus, control group – 36 individuals. The patients underwent MRI with measurement and evaluation of the optic nerve sheath diameter (ONSD), the optochiasmal cistern and the pituitary gland vertical sizes, and tortuosity of the ON. Patients of the 2nd group underwent a phase-contrast MRI with an assessment of the velocity and volumetric characteristics of blood and cerebrospinal fluid flows with the calculation of the intracranial compliance index (ICC). Using the FreeSurfer program, the brain volumes were estimated. Results and discussion. A statistically significant increase in ONSD was found in the groups of patients compared with the control group (by 24 %, p < 0.05), decrease in the vertical size of the pituitary gland and an increase in the vertical size of the optochiasmal cistern (p < 0.05), as well as ICC lowering in group 2 (by 1.7 times, p < 0.05). Tortuosity of ON in group 1 was observed more often than in other groups. A statistically significant positive correlation between ONSD and brain volumes in group 1 (r = 0.55, p < 0.05) and a negative correlation between brain volumes and ICC in group 2 (r = –0.86, p < 0.05) has been found. Conclusions. Based on the presented results, we believe that the combined use of qualitative and quantitative MRI criteria can expand the diagnostic capabilities of non-invasive assessment of increased intracranial pressure.